2015
DOI: 10.5120/20816-3205
|View full text |Cite
|
Sign up to set email alerts
|

Design of Digital Respiration Rate Meter

Abstract: In this paper, we describe The Digital Respiration Rate Meter, a device used to measure the rate of respiration. It consists of a transmitter section, receiver section and breathing setup. Transmitter section transmits IR waves which are cut by a displacement transducer in the breathing setup. This IR wave is sensed by the receiver section. The Controller section reads this and generates the count to be displayed. This is displayed on three seven-segment displays for read out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…The proposal is a remote-controlled drone o helicopter that has an average price of $ 800-2500 plus a sprayer of $ 400-500 would average an average of around $1,200-3,000 against the $ 13,500-15,000 of a fumigator drone. The main limitation for aerial applications of agrochemicals is the ability of the drone [6] Design the drone that is unmanned aerial vehicle (UAV) for agricultural purpose for spraying pesticides India [7] Proposes a new mission assignment scheme aimed at the farmland spraying problem. A simulation platform is established and a series of simulations are carried out to verify the reasonability and correctness of this scheme [8] Developed a low volume spray system for use on a fully autonomous UAV to apply crop protection products on specified crop areas.…”
Section: Resultsmentioning
confidence: 99%
“…The proposal is a remote-controlled drone o helicopter that has an average price of $ 800-2500 plus a sprayer of $ 400-500 would average an average of around $1,200-3,000 against the $ 13,500-15,000 of a fumigator drone. The main limitation for aerial applications of agrochemicals is the ability of the drone [6] Design the drone that is unmanned aerial vehicle (UAV) for agricultural purpose for spraying pesticides India [7] Proposes a new mission assignment scheme aimed at the farmland spraying problem. A simulation platform is established and a series of simulations are carried out to verify the reasonability and correctness of this scheme [8] Developed a low volume spray system for use on a fully autonomous UAV to apply crop protection products on specified crop areas.…”
Section: Resultsmentioning
confidence: 99%
“…]. At the average breathing rate reported in healthy adults at rest is usually administered as 12 breaths per minute (12⋅60 Hz) but estimates vary between sources for example, 12-20 breaths per minute, 10-14, between 16-18, etc [9]. RR that leads to bradypnea (RR <12) or even apnea (respiratory cessation for an indence period) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because of human nature that is easy to forget, tired, and bored, it is now widely developed the method of measuring or observing breathing rates electronically [2]. A study comparing respiration measurement using a calculator and manual measurement showed the benefits of using digital counting techniques [7]. Larasati has perfected the module by displaying the output on a TFT LCD and using a humidity sensor.…”
Section: Introductionmentioning
confidence: 99%